Effectiveness of isokinetic exercise on paind and function in patiensts with total knee arthroplasty - Dulgeroglu , Deniz; Ozen , Natalya; Tezel , Nihal; Tombak , Yasemin; Aykin , Zeynep (Annals of Medical Research, 2022)
Aim: Relief of pain and physical function improvements normally happen in 6 to 12 months following total knee arthroplasty (TKA). Neverthless, pain persists in some patients even after one year. Likewise, functional improvement is insufficient. We have evaluated the effectiveness of an isokinetic strengthening program on post-operativelly (1-9 years) knee pain, funtional limitation, level walking and stair climbing in patients with TKA at late period. Methods: Twenty-five women patients with TKA were assigned into isokinetic training (study group) or the control groups. Patients answered WOMAC questionnaire and performed Stair Climbing Test. Quadriceps and hamstring muscle strength were evaluated isokinetically at 60 and 180°/sec angular velocity. All tests were evaluated before & after intervention and at follow-up three months later. Only the study group performed isokinetic training five days a week for two weeks while both groups received home-based exercise program. Results: Knee pain at rest and during walking statistically decreased in both groups as per the evaluations at before & after intervention and 3-month follow-up. Comparison of WOMAC scores in two groups revealed only a statistically significant decrease in the study group among the after intervention & follow-up values. Although the increase at 60°/sec extension and flexion PT values in the study group was greater than that in the control group, there was no pointed difference between both groups. Conclusion: Strengthening of the knee muscles with isokinetic exercise reduces pain and improves functionality more than the home-based exercise program does. Registration: The study was approved by the Ethics Committee in the University of Health Sciences, Diskapi Training and Research Hospital (Protocol #34/09 Dated 16.01.2017).